Safety of contraceptive use among women with congenital heart disease: A systematic review. (25th January 2019) - Abarbanell, Ginnie; Tepper, Naomi K.; Farr, Sherry L.
Abstract: Objective: Women with congenital heart disease (CHD) are at increased risk of pregnancy complications and need information on safe, effective contraceptive methods to avoid unintended pregnancy. This systematic review examines evidence regarding safety of contraceptive use among women with CHD. Methods: The PubMed database was searched for any peer‐reviewed articles published through April 2018 that included safety outcomes associated with reversible contraceptive methods among women with CHD. Results: Five articles met inclusion criteria: three studies comparing contraceptive users to nonusers and two noncomparative studies. Sample sizes ranged from 65 to 505 women with CHD. Two studies found a higher percent of thromboembolic complications among women with Fontan palliation or transposition of the great arteries using oral contraceptives. One study, among women with Fontan palliation, found no increased risk of thromboembolic complications between contraceptive users (not separated by type) and nonusers. Two studies found no endocarditis among intrauterine device users. Conclusions: There is a paucity of data regarding the safety of contraceptive methods among women with CHD. Limited evidence suggests an increased incidence of thromboembolic complications with use of oral contraceptives. Further studies are needed to evaluate contraceptive safety and quantify risk in this growing population. There is also limited data regarding the safety of contraceptive methods among women with CHD. Further information is needed to assist practitioners counseling women with CHD on safety of contraceptive methods.